Facilitating the Delivery of Cognitive Remediation in First-Episode Psychosis: Pilot Study of a Home-Delivered Web-Based Intervention. Issue 11 (November 2019) - Moura, Bernardo Melo; Avila, Alessia; Chendo, Inês; Frade, Patrícia; Barandas, Rita; Vian, João; Croca, Marta; Roberto, Alice; Almeida, Carolina; Antunes, Filipa; Linhares, Ludgero; Crawford, Joana; et al.
Abstract : Abstract: We explored the adherence to a home-delivered, computer-based, cognitive remediation protocol in a first-episode psychosis outpatient cohort. Seventeen patients underwent a cognitive training protocol for 6 months using an online platform accessible from their home under the supervision of a qualified neuropsychologist. Neuropsychological, psychopathological, and functional data were collected at baseline and postintervention, whereas qualitative appraisal of the intervention was assessed monthly. Overall, participants' evaluation of the program was positive. This was reflected in a good adherence rate with 12 (70%) of 17 patients completing 80% of the prescribed sessions. Exploratory analysis revealed significant improvements in sustained attention ( p = 0.020) and verbal memory ( p = 0.018). A decrease in negative symptoms and an improvement on the Clinical Global Impression were also found ( p = 0.009). We believe these are encouraging results to further explore the adopted delivery approach, which could facilitate access to cognitive training earlier and to a larger group of patients. Abstract : Supplemental digital content is available in the text.